The Implemention Of Cooperative Script Learning Model Toward Students’ Achievement In Ipa Lesson On Healthy Environment Materials And Environment Unhealthy At Third Grade Students’ In Sdn 05 Perawang In Academic Year 2016/2017 - Mariati Mariati (Fakultas Sastra Universitas Ekasakti, 2018)
Based on observations made through interviews and direct observation in SD Negeri 05 Tualang, in the learning process there are obstcles, including student learning outcomes are still low. The condition is clearly visible from the average value of the daily tests conducted earlier IPA as many as 100 students (66.66%) of the 3 classes that reach KKM 75. Based on the problem above, the problem in this research is